2018
DOI: 10.3844/ajassp.2018.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance and Evaluation of Genetic Changes in Rice Mutant Lines

Abstract: The genetic improvement of rice through mutation induction to obtain drought resistance is essential for stable and adequate rice production would enable us to anticipate the rice yield-reducing effects of global warming. The aim of this research was to evaluate the rice mutant lines showing tolerance to drought condition and their genetic relationship using SSR markers. Mutant lines were obtained by irradiation of Mira-1 rice variety at primordial state by 25 and 50 Gy doses. Twenty numbers of M4 rice mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Abiotic stress is defined as the detrimental effect of non-living factors on plants in a specific environment including drought, floods, salinity, extreme temperature, heavy metals, and other natural causes. Herwibawa, Sakhidin & Dwi Haryanto (2019) , Amsal & Ishak-Ishak (2018) , Yunita et al (2020) , Meesook, Pongtongkam & Poeaim (2018) , Che Mohd Zain et al (2016) , and Kadhimi et al (2016a) , for example, have conducted research to identify drought-resistant rice cultivars. Researchers from Malaysia, Che Mohd Zain et al (2016) and Kadhimi et al (2016b) exposed rice seeds (MRQ74 and MR269) to 350 Gy of gamma rays and generated osmotic stress using a varied concentration of Polyethylene glycol (PEG) 6,000 ranging from 0–20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic stress is defined as the detrimental effect of non-living factors on plants in a specific environment including drought, floods, salinity, extreme temperature, heavy metals, and other natural causes. Herwibawa, Sakhidin & Dwi Haryanto (2019) , Amsal & Ishak-Ishak (2018) , Yunita et al (2020) , Meesook, Pongtongkam & Poeaim (2018) , Che Mohd Zain et al (2016) , and Kadhimi et al (2016a) , for example, have conducted research to identify drought-resistant rice cultivars. Researchers from Malaysia, Che Mohd Zain et al (2016) and Kadhimi et al (2016b) exposed rice seeds (MRQ74 and MR269) to 350 Gy of gamma rays and generated osmotic stress using a varied concentration of Polyethylene glycol (PEG) 6,000 ranging from 0–20%.…”
Section: Resultsmentioning
confidence: 99%
“…Under the drought stress level of −0.03 MPa, the genetic variants in the M1 generation show diversity, and the best combination of mutagen and cultivar is Inpago Unsoed 1, which was irradiated with gamma-ray 100 Gy and then soaked in SA for 2 h ( Herwibawa, Sakhidin & Dwi Haryanto, 2019 ). Amsal & Ishak-Ishak (2018) exposed the Mira-1 rice variety to 25 and 50 Gy of gamma rays and tested with 20% PEG resulting in two (2) from 20 mutant lines; 28H1 and 30F1 mutant lines showing the best characteristics (number of productive tillers; 12 each, lateral root; 142 and 100, and grain yield per panicle; 80 and 124, respectively) for drought tolerant. Lateral roots can develop on any primary root, including crown roots and embryonic, and are used as a drought tolerance indicator.…”
Section: Resultsmentioning
confidence: 99%
“…The number of productive tillers affects grain yield. Productive tillers will produce panicles, so the more productive tillers, the higher the number of panicles obtained [20]. Drought stress significantly affected the number of productive tillers of M4 Boyolali variety (Table 3).…”
Section: Number Of Productive Tillersmentioning
confidence: 98%
“…The root system size affects the absorption of water and minerals from the soil and is related to the size of the plant part above the soil surface [25]. The statistical tests showed that rice cultivars significantly affected the shoot-root ratio.…”
Section: Shoot-root Ratiomentioning
confidence: 99%